2006
DOI: 10.1002/dvdy.20957
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchy of Runx transcription factors modulate the onset of chondrogenesis in craniofacial endochondral bones in zebrafish

Abstract: The Runx (runt-related) family of transcription factors are important regulators of cell fate decisions in early embryonic development, and in differentiation of tissues including blood, neurons, and bone. During skeletal development in mammals, while only Runx2 is essential for osteoblast differentiation, all family members seem to be involved in chondrogenesis. Runx2 and Runx3 control chondrocyte maturation. Both Runx1 and Runx2 are expressed early in mesenchymal condensations, but how they contribute to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
89
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 75 publications
(99 citation statements)
references
References 60 publications
9
89
1
Order By: Relevance
“…Several stage-46 clearedand-stained tadpoles injected with both morpholinos lack cranial trabeculae and otic capsules (Fig. 4B), as has been demonstrated for zebrafish runx2b-II (Flores et al, 2006). However, many hatchlings recover from the effect of morpholinos by this stage.…”
Section: Runx2 In Larval Xenopus 1657supporting
confidence: 65%
See 4 more Smart Citations
“…Several stage-46 clearedand-stained tadpoles injected with both morpholinos lack cranial trabeculae and otic capsules (Fig. 4B), as has been demonstrated for zebrafish runx2b-II (Flores et al, 2006). However, many hatchlings recover from the effect of morpholinos by this stage.…”
Section: Runx2 In Larval Xenopus 1657supporting
confidence: 65%
“…5). This stronger effect is shared with the zebrafish runx2b-II morpholino in comparison with runx2b-I (Flores et al, 2006). Mouse cell culture studies also have found the RUNX2-II protein to have a greater effect on regulating the osteocalcin gene than RUNX2-I (Harada et al, 1999), which indicates a stronger role for this isoform as a transcription factor during bone formation.…”
Section: Isoform-specific Differencesmentioning
confidence: 96%
See 3 more Smart Citations